Problem efektywności banków w literaturze przedmiotu - Kubiszewska, Katarzyna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The purpose of this article is to analyze the literature related to the problem ofbank effectiveness. The article is divided into three parts. The first one is devotedto the various concepts of effectiveness. The second part discusses the methodsand tools used to measure the level of efficiency of a banking market. The thirdpart presents results of selected studies on this issue, with a special emphasis onthe banking sectors of economies during systematic transformation.